The Middleman Economy - Krakovsky, Marina. author. aut Link
VII, 229 p.
Keywords: With the rise of the Internet, many pundits predicted that middlemen would disappear. But that hasn't happened. Far from killing the middleman, the Internet has generated a thriving new breed. In The Middleman Economy , Silicon Valley-based reporter Marina Krakovsky elucidates the six essential roles that middlemen play.